Gut Microbiota Modulation for Multidrug-Resistant Organism Decolonization: Present and Future Perspectives - Gargiullo, Livia; Del Chierico, Federica; D’Argenio, Patrizia; Putignani, Lorenza (Frontiers in Microbiology, 2019)
The emergence of antimicrobial resistance (AMR) is of great concern to global public health. Treatment of multi-drug resistant (MDR) infections is a major clinical challenge: the increase in antibiotic resistance leads to a greater risk of therapeutic failure, relapses, longer hospitalizations, and worse clinical outcomes. Currently, there are no validated treatments for many MDR or pandrug-resistant (PDR) infections, and preventing the spread of these pathogens through hospital infection control procedures and antimicrobial stewardship programs is often the only tool available to healthcare providers. Therefore, new solutions to control the colonization of MDR pathogens are urgently needed. In this narrative review, we discuss current knowledge of microbiota-mediated mechanisms of AMR and strategies for MDR colonizzation control. We focus particularly on fecal microbiota transplantation (FMT) for MDR intestinal decolonization and report updated literature on its current clinical use.